Vivere est cogitare. Szkic o dorobku naukowym prof. Marii Zmierczak - Urbańczyk, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The aim of the paper is presentation of the most significant scientific interests of a full professor and post-doctorate degree Maria Zmierczak, reputed and prominent scholar of history of political and legal doctrines, for many years head of the Chair of Political and Legal Doctrines and Philosophy on the Faculty of Law and Administration at Adam Mickiewicz University in Poznań.The scientific interests of Professor Maria Zmierczak include the classical political doctrines of 19th and 20th century and chosen legal doctrines of 20th century. Among the first ones the most compelling is the research on history and the evolution of liberalism and the study on totalitarianism and fascism. The other issues analyzed by Professor Maria Zmierczak consist of the research on the Renaissance of the natural law after the Second World War and the study on the rule of law.
Keywords: Zmierczak Maria; liberalizm; faszyzm; nazizm; totalitaryzm; praworządność; doktryny polityczne i prawne